A genomic perspective on the taxonomy of the subtribe Carcharodina (Lepidoptera: Hesperiidae: Carcharodini) - Zhang, Jing; Brockmann, Ernst; Cong, Qian; Shen, Jinhui; Grishin, Nick V. (Zootaxa, 2020)
We obtained whole genome shotgun sequences and phylogenetically analyzed protein-coding regions of representative skipper butterflies from the genus Carcharodus Hübner, [1819] and its close relatives. Type species of all available genus-group names were sequenced. We find that species attributed to four exclusively Old World genera (Spialia Swinhoe, 1912, Gomalia Moore, 1879, Carcharodus Hübner, [1819] and Muschampia Tutt, 1906) form a monophyletic group that we call a subtribe Carcharodina Verity, 1940. In the phylogenetic trees built from various genomic regions, these species form 7 (not 4) groups that we treat as genera. We find that Muschampia Tutt, 1906 is not monophyletic, and the 5th group is formed by currently monotypic genus Favria Tutt, 1906 new status (type species Hesperia cribrellum Eversmann, 1841), which is sister to Gomalia. The 6th and 7th groups are composed of mostly African species presently placed in Spialia. These groups do not have names and are described here as Ernsta Grishin, gen. n. (type species Pyrgus colotes Druce, 1875) and Agyllia Grishin, gen. n. (type species Pyrgus agylla Trimen, 1889). Two subgroups are recognized in Ernsta: the nominal subgenus and a new one: Delaga Grishin, subgen. n. (type species Pyrgus delagoae Trimen, 1898). Next, we observe that Carcharodus is not monophyletic, and species formerly placed in subgenera Reverdinus Ragusa, 1919 and Lavatheria Verity, 1940 are here transferred to Muschampia. Furthermore, due to differences in male genitalia or DNA sequences, we reinstate Gomalia albofasciata Moore, 1879 and Gomalia jeanneli (Picard, 1949) as species, not subspecies or synonyms of Gomalia elma (Trimen, 1862), and Spialia bifida (Higgins, 1924) as a species, not subspecies of Spialia zebra (Butler, 1888). Sequencing of the type specimens reveals 2.2-3.2% difference in COI barcodes, the evidence that combined with wing pattern differences suggests a new status of a species for Spialia lugens (Staudinger, 1886) and Spialia carnea (Reverdin, 1927), formerly subspecies of Spialia orbifer (Hübner, [1823]).